Since triangles \( ∆XYZ \) and \( ∆RST \) are similar (indicated by \( ∆XYZ ∼ ∆RST \)), their corresponding angles are equal.
We know:
- \( m∠X = 50° \)
- \( m∠S = 79° \)
To find \( m∠T \), we first calculate \( m∠Y \) since the angles in a triangle sum to \( 180° \):
\[ m∠Y = 180° - m∠X - m∠Z \]
But we need to find \( m∠Z \) in terms of \( m∠R \) because of the similarity.
Thus:
- For triangle \( ∆RST \):
\[ m∠R + m∠S + m∠T = 180° \]
So, we need to determine \( m∠R \) based on the corresponding angle \( m∠Y \) from triangle \( ∆XYZ \):
\[ m∠Y = m∠R \]
Now, compute \( m∠Y \):
\[ m∠Y = 180° - m∠X - m∠Z \] However, we do not have \( m∠Z \) directly, so we must sum the known angles.
From \( \triangle RST \):
- \( m∠R = m∠Y \)
- \( m∠S = 79° \)
Thus:
\[ m∠Z + m∠Y + m∠S = 180° \] \[ m∠Z + 50° + 79° = 180° \] \[ m∠Z + 129° = 180° \] \[ m∠Z = 51° \]
The last angle is:
\[ m∠T + m∠S + m∠R = 180° \] \[ m∠T + 79° + 51° = 180° \] \[ m∠T + 130° = 180° \] \[ m∠T = 50° \]
Thus, \( m∠T = 50° \).
Hence, the measure of angle \( T \) is:
\[ \boxed{50°} \]